STUDI EVALUASI PERENCANAAN JARINGAN DAERAH IRIGASI PERDAMAIAN SINGKUT KABUPATEN SAROLANGUN PROVINSI JAMBI - Aasniari Aasniari; Eko Noerhayati; Bambang Suprapto (Universitas Islam Malang, 2020)
The]Perdamaian]Irrigation]Area]is]one]of the]irrigation areas in]Sarolangun Regency]which has a]255]hectarepaddy field]area. In the Village of ]Peace there]are]paddy]fields]where irrigation]channels are inadequate soflooding]often]occurs]when]the]intensity]of]rain]is]high. The irrigation]network in the Perdamaian]irrigation]area isa fairly]fertile area,]but it needs attention in]terms]of]improvement]and]physical]facilities]in its irrigation. Thepurpose of this study was to determine the existing conditions in the network channel, to know the mainstaydischarge, to know the level of water efficiency in the channel, to know the dimensions of the planned networkchannel in order to]accommodate]rainwater. This]research]was]conducted]in]the]Singkut]Perdamaian]area]ofSarolangun]Regency, Jambi]Province. In]this]study]the]plan]discharge]was]used]to]plan]the]irrigation]networkchannel. ]Channel]1]is]unable to]load]and]drain the]water flow to be]flowed]so]a]re-planning is needed because theexisting]channel discharge]is 4.92 m3 / sec]while]the]planned]discharge is]8.42]m3 / sec, with the economicdimensions of the trepesium channel as big as the base width of the channel (B) = 2.50 m, water level](h)]= 1.80 m,a debit (Q)]of ]10.63]m3 / s is obtained. With]the]evaluation]of ]the]channel]dimension]plan, the]network]channel is able]to]accommodate]the flow of water]that]will flow]through the]rice fields]so]that]there is]no]flooding. ]Keywords:]Dimension]of]economic]channels,]Irrigation]Perdamaian]Sarolangun]Jambi]